2021
DOI: 10.1021/acs.iecr.1c02565
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Ni/AC Catalyst for Low-Temperature CO-Selective Catalytic Denitration Mechanism

Abstract: To study the preparation principle of Cu−Ni/AC catalysts and the mechanism of low-temperature CO-selective catalytic reduction (SCR) denitration, Cu−Ni/AC catalysts with different metal loadings were prepared by the isometric ultrasonic impregnation method. It was determined that the 10Cu−4Ni/AC catalyst had the best CO-SCR low-temperature denitration rate of 94.2% in 5% O 2 and at the denitration temperature of 150 °C. The characterization of Cu−Ni/AC by scanning electron microscopy (SEM), Brunauer−Emmett−Tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Nitrogen oxides (NO x ), as the primary atmospheric pollutants produced by the combustion of carbon-based fuels, have posed risks to both ecology and human health, such as ozone depletion, greenhouse effect, and lung diseases. With increasingly stringent standards on NO x emissions, nitrogen removal technologies have attracted tremendous attention in recent years. Wherein selective catalytic reduction of NO x by CO (CO-SCR) shows immense potential, especially in applications with notable CO generation, including power plant boilers, vehicle exhaust, and activated carbon regeneration gas. , It can avoid the drawbacks of the industrial NH 3 -SCR process (e.g., ammonia escape, toxicity, and equipment corrosion), as well as facilitating simultaneous removal of multiple pollutants. , Recently, cost-effective transition metal-based catalysts have drawn widespread research interest for CO-SCR with superb activities competitive to noble metal contained materials. , …”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides (NO x ), as the primary atmospheric pollutants produced by the combustion of carbon-based fuels, have posed risks to both ecology and human health, such as ozone depletion, greenhouse effect, and lung diseases. With increasingly stringent standards on NO x emissions, nitrogen removal technologies have attracted tremendous attention in recent years. Wherein selective catalytic reduction of NO x by CO (CO-SCR) shows immense potential, especially in applications with notable CO generation, including power plant boilers, vehicle exhaust, and activated carbon regeneration gas. , It can avoid the drawbacks of the industrial NH 3 -SCR process (e.g., ammonia escape, toxicity, and equipment corrosion), as well as facilitating simultaneous removal of multiple pollutants. , Recently, cost-effective transition metal-based catalysts have drawn widespread research interest for CO-SCR with superb activities competitive to noble metal contained materials. , …”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, scholars have conducted research on the effect of the catalyst support. , Some prominent results have been obtained in the research on TiO 2 , Al 2 O 3 , SiO 2 , molecular sieves, and carbon-based materials, but the applications of these supported catalysts have been limited by the high cost, recycling, and hydrothermal stability problems. , It is worth noting that activated carbon, such as rice husk char, has a strong adsorption capacity and deoxidizing ability to promote the reaction between CO and NOx . Additionally, the abundant inner surface and uniform pore size of SiO 2 mesoporous materials make them be used widely in catalysis, catalytic supports, and molecular adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that active metal components can be loaded into AC to improve its low-temperature denitration activities. The metals used as active components are mainly iron (Fe), 9 manganese (Mn), 10 copper (Cu), 6 cobalt (Co), 11 cerium (Ce), 10,11 platinum (Pt), 12 palladium (Pd), 13 rhodium (Rh), 14 and silver (Ag), 14,15 of which Mn has good low-temperature denitration activity. 16 In the field of NH 3 -SCR denitration, J. Y. Chen et al 17 found that MnO x loaded into Fe 2 O 3 /AC increases amorphous dispersion, the Fe 3+ /(Fe 3+ + Fe 2+ ) and Mn 4+ /Mn 3+ ratio, specific surface area, and pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…4 Carbon monoxide (CO) and ammonia (NH 3 ) are reducing agents for SCR. One technical advantage of CO-SCR 5,6 is that CO exists in automobile exhaust and industrial exhaust gases. Using it as a reducing agent to treat NO x treats waste with waste; however, this method has challenges.…”
Section: Introductionmentioning
confidence: 99%